Root physiological adaptations involved in enhancing P assimilation in mining and non-mining ecotypes of Polygonum hydropiper grown under organic P media - Ye, Daihua; Li, Tingxuan; Zheng, Zicheng; Zhang, Xizhou; Chen, Guangdeng; Yu, Haiying (Frontiers in Plant Science, 2015)
It is important to seek out plant species, high in phosphorus (P) uptake, for phytoremediation of P-enriched environments with a large amount of organic P (Po). P assimilation characteristics and the related mechanisms of Polygonum hydropiper were investigated in hydroponic media containing various concentrations of Po (1-8 mmol L-1) supplied as phytate. The mining ecotype (ME) showed significantly higher biomass in both shoots and roots compared to the non-mining ecotype (NME) at 4, 6, and 8 mmol L-1. Shoot P content of both ecotypes increased up to 4 mmol L-1 while root P content increased continually up to 8 mmol L-1 for the ME and up to 6 mmol L-1 for the NME. Root P content of the ME exceeded 1% dry weight under 6 and 8 mmol L-1. The ME had significantly higher P accumulation in both shoots and roots compared to the NME supplied with 6 and 8 mmol L-1. The ME showed higher total root length, specific root length, root surface area, root volume and displayed significantly greater root length, root surface area, and root volume of lateral roots compared to the NME grown in all Po treatments. Average diameter of lateral roots was 0.17-0.19 mm for the ME and 0.18-0.21 mm for the NME. Greater acid phosphatase and phytase activities were observed in the ME grown under different levels of Po relative to the NME. This indicated fine root morphology, enhanced acid phosphatase and phytase activities might be adaptations to high Po media. Results from this study establish that the ME of P. hydropiper is capable of assimilating P from Po media and is a potential material for phytoremediation of polluted area with high Po.